CLINICAL AND LABORATORY FEATURES OF VITAMIN B12 DEFICIENCY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Vitamin B12 plays an essential role in DNA synthesis, methylation, and neurological function. Deficiency of vitamin B12 is a common clinical problem, especially among elderly individuals, vegetarians, patients with gastrointestinal disorders, and those receiving long-term metformin or proton pump inhibitor therapy. Clinical manifestations may include macrocytic anemia, glossitis, peripheral neuropathy, cognitive impairment, and neuropsychiatric disorders, although neurological symptoms may occur even in the absence of anemia. Early diagnosis remains challenging because serum cobalamin levels do not always reflect functional deficiency. Modern laboratory diagnostics include the assessment of homocysteine, methylmalonic acid, and holotranscobalamin levels, which improve diagnostic accuracy. This review discusses the pathogenesis, clinical manifestations, and modern diagnostic approaches to vitamin B12 deficiency.
Keywords: vitamin B12 deficiency, macrocytic anemia, homocysteine, methylmalonic acid, holotranscobalamin, laboratory diagnostics.